Future of maritime education and training : blending hard and soft skills - Geada Borda de Água, Pedro Manuel (Array, 2020)
The 21st century endeavour bring new challenges for the maritime industry. The challenges facing the professionals within the industry are multifaceted and complex due to globalization, cross-cultural interrelationships, and technological change that are permeating the maritime industry. The aim of this article is to contribute to better understanding the problem of developing the future maritime industry professional, filling the existing gap between education and training programmes, while integrating the 21st century professional skills. The contents of a comprehensive education and training programme shall be proposed within a knowledge triangle encompassing academia, the industry and relevant authority or regulatory institutions, so all interested parties’ “voices” will be considered. Besides raising awareness for the educational and training challenges ahead, more effective teaching methods are suggested in order to meet the needs, particularly supporting double loop learning, together with a pragmatic proposal for a realistic programme at master’s level. The proposed programme is based on the EU MarLEM project, which aims towards the development of the 21st century maritime industry professional, focusing on logistics, engineering and management contents.